The Growth and Productive Performance of Tectona grandis Linn. F. in Plantations and Farmlands in Upper Zone (Upghat) of Uttara Kannada District of Karnataka (India) - Shahapurmath, Girish; Hanumantha, M.; Rashmi, V. (Indian Forester, 2018)
The experiment was conducted to understand the growth performance and productivity potential of Tectona grandis grown in plantation as well as in the farmlands at upper zone of Uttara Kannada district of Karnataka. The growth of teak tree grown in farmland was significantly higher than tree grown in pure plantation. For instance, the overall height(13.43 m), diameter (26.05 cm), clear bole height (7.46 m), tree volume (0.800 m3) and timber volume (0.463 m3) were higher in farmland than trees grown in pure plantation (11.68 m, 22.90 cm, 5.93 m, 0.635 m3 and 0.337 m3, respectively). However, crown parameters did not show significant difference among trees grown in pure plantations and farmlands. There was a strong influence of age on growth of teak trees grown in both farmland and pure plantation. For instance, tree height (15.45 m) and diameter (33.39 cm) of higher age class (A4: 21-25 years) were maximum as compared lower age class (A1: 5-10 years) with values of 7.89 m and 16.05 cm, respectively. Similar trend was also recorded for volume, clear bole height, crown height, crown length and crown diameter in teak. It is concluded that teak grown in farmland produce higher growth and volume as compared to pure plantation, since management practices and cultural operations are regularly undertaken in the farmlands; however, regular management is scanty in pure plantation which is need to be tackled to get more productivity.